Efficacy of commercial insecticides for cowpea pod borer (Maruca vitrata F.) management in Pokhara, Nepal (Journal of Agriculture and Natural Resources, 2021)
Cowpea (Vigna unguiculata Walp.) is a major grain legume used as vegetables and pulses. Among the several insect pest of cowpea, spotted pod borer is one of the most destructive pest. To evaluate the available chemical pesticides for pod borer management, a set of field experiments on cowpea variety Malepatan-1 were conducted at Horticulture Research Station, Malepatan, Pokhara in years 2019 and 2020. The experiments were laid out in Completely Randomized Block Design (RCBD) having seven  treatments viz.Flubendiamide 39.35 % SC @ 0.3 mL/L, Chlorantraniliprole 18.5 % SC @ 0.2 mL/L, Emamectin benzoate 5 % SG @0.3 g/L, Spinosad 45 % SC @0.3 mL/L, Bacillus thuringiensis Kurstaki @2g/L, Azadirechtin 0.03%@ 5mL/L and Control with four replications. Flubendiamide 39.35 % SC @ 0.3 mL/L and Emamectin benzoate 5 % SG @0.3 g/L were found the most effective insecticides in lowering cowpea flower and pod damage with highest benefit cost ratio; however, considering environment, Chlorantraniliprole 18.5 % SC @ 0.2 mL/L and Spinosad 45 % SC @0.3 mL/L being next effective treatments could be viable option to manage spotted pod borer in cowpea production.